Анализа корелације нивоа CD354 и ANGPT2 у серуму са прогнозом сепсе: Нивои серума CD354 и ANGPT2 у прогнози сепсе - Luo, Mingying; Hong, Yun; Chen, Junhao; Fu, Cong (Journal of Medical Biochemistry, 2026)
[Objective] To explore the changes of procalcitonin (PCT), Angiopoietin-2 (ANGPT2), and serum Cluster of Differentiation 354 (CD354) concentrations in pediatric sepsis patients. [Methods] 190 children with sepsis who were hospitalized to our hospital between January 2024 and June 2025 had their clinical data analyzed retrospectively. Based on the severity of their conditions, the patients were divided into a severe group (n = 84) and a nonsevere group (n = 106). A survival group (n = 134) and a death group (n = 56) were created based on the prognosis of the two groups of children within 28 days after admission. Serum levels of CD354, ANGPT2, and PCT in the severe and nonsevere groups were compared, and the predictive efficacy of these indicators alone or in combination for assessing the severity of sepsis in children was determined using receiver operating characteristic (ROC) curves. The differences in serum CD354, ANGPT2 and PCT levels between the survival group and the death group were compared, and the predictive efficacy of these indicators alone or in combination for evaluating the prognosis of sepsis in children was determined using receiver operating characteristic (ROC) curves. [Results] The serum CD354, ANGPT2 and PCT levels were higher in the severe group than in the nonsevere group (P < 0.05). The sensitivity and specificity of serum CD354 for evaluating the severity of sepsis in children were 92.48% and 66.60%, respectively. The sensitivity and specificity of serum ANGPT2 for evaluating the severity of sepsis in children were 94.37% and 88.13%, respectively. The sensitivity and specificity of serum PCT for evaluating the severity of sepsis in children were 94.37% and 66.60%, respectively. The sensitivity and specificity of serum ANGPT2 for evaluating the severity of sepsis in children were 94.37% and 88.13%, respectively. The sensitivity and specificity of serum PCT for evaluating the prognosis of sepsis in children were 64.22% and 100.00%, respectively. Children who died had greater levels of serum CD354, ANGPT2, and PCT than children who survived (P < 0.05). For assessing the prognosis of sepsis in children, serum CD354 has sensitivity of 53.50% and specificity of 83.51%. Serum ANGPT2 has sensitivity and specificity of 82.17% and 98.54%, respectively, for assessing the prognosis of sepsis in children. The sensitivity and specificity of serum PCT for evaluating the prognosis of sepsis in children were 64.22% and 100.00%, respectively. [Conclusion] Serum CD354, ANGPT2 and PCT levels significantly guide the assessment of the severity of the condition in children with sepsis and provide important reference values for prognosis.